Vidyaranyamuni 'ten men story' from Panchadasi as an illustration for Advaitic 'self-realization' - Ravi Kumar Reddy Juturi (Wolters Kluwer Medknow Publications, 2021)
The article dwells on a Mantra from Brihadaranyaka Upanishad. This Mantra contains the essence of Vedanta. Vidyaranya Muni in Panchadasi Text writes the biggest chapter (seventh chapter) 290 Verses on this one Mantra. Four aspects are to be understood from this Mantra to understand the spiritual process in Advaitic realization. The first one is the realization, which means realizing who or what am 'I' truly (individual 'I' or Jiva). As a result, the negation of worldly enjoyments (Bogya Nisheda) means nothing in this world becomes an object worth pursuing, so one transcends this stage. The next aspect of the Mantra signifies for whose sake am 'I' (Jiva) doing all this? Hence, the 'enjoyer' or the 'person' who is trying to get pleasures, satisfaction, and enjoyment in this world must inquire into 'that;' it is nothing but the negation of the enjoyer (Boktri Nisheda). The third aspect of Mantra deals with what is there to be desired in this world from the point of realized 'self'. As a result of this process, the 'One' who thinks an 'individual being' having the body and mind and trying to attain certain goals in life, that 'One' is dissolved. Finally, suffering along with the 'body and mind' complex is transcended, this is called liberation while living (Jivanmukti); it means that life continues with the body and mind but amidst this 'realized one' transcends suffering; this is called living in the body yet transcending the body. These four aspects have dwelled in this article with the help of 'Ten men story' from a sacred text called Panchadasi written by Vidyaranya Muni.